2022
DOI: 10.47352/jmans.2774-3047.143
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Doogh with Olive Leaf Extract and Investigation of Its Physicochemical, Microbial, and Sensory Properties during Storage at Room Temperature and Refrigerator

Abstract: Doogh is a popular Iranian drink with high nutritional value and in recent years has attracted the attention of many consumers. Nowadays, the problems caused by malnutrition and lack of useful compounds with high nutritional value and increasing shelf life are essential in the food industry. This research was performed in Shirin Cheshmeh Dairy Production Company and all experiments were performed in the Food Control Laboratory of the Food and Drug Administration, Guilan University of Medical Sciences. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In folk medicine, EOs and extracts of peppermint have been widely used to treat inflammation of the oral mucosa, and cold. The EOs of peppermint have been reported to have antioxidant, antiinflammatory, antibacterial, and antifungal activities [11]- [13]. Therefore, this study aimed to use edible nontoxic clove and peppermint essential oils to prevent the colonization of pathogenic gut microbiota in patients with chronic hepatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…In folk medicine, EOs and extracts of peppermint have been widely used to treat inflammation of the oral mucosa, and cold. The EOs of peppermint have been reported to have antioxidant, antiinflammatory, antibacterial, and antifungal activities [11]- [13]. Therefore, this study aimed to use edible nontoxic clove and peppermint essential oils to prevent the colonization of pathogenic gut microbiota in patients with chronic hepatic disease.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the popularity of this fermented beverage arises from its organoleptic characteristics and its health benefits [1][2][3][4] . Doogh is the result of the lactic fermentation of milk and similar products are consumed in some countries in the Middle East and Central Asia [5][6][7] . Milk and dairy products are relatively adequate foods and are good sources of mineral nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that the effect of olive leaf extract on the pH, mould, and yeast of the treatments is decreasing and the percentage of acidity and serum volume is increasing. In general, according to their results, it can be noted that the production of useful products with plant compounds can promote an effective step to produce and design useful drinks in the consumer market and food industry factories [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, their study revealed that Chaerophyllum, Oliveria and Zataria essential oils can apply as natural antimicrobial agents in Doogh [3]. Kalavari et al (2022) assessed the physicochemical, microbial, and sensory properties of Doogh enriched with olive leaf extract during 45 days storage. Their study showed that the effect of olive leaf extract on the pH, mould, and yeast of the treatments is decreasing and the percentage of acidity and serum volume is increasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation